PROGRAM BIMBINGAN KARIR UNTUK MENINGKATKAN KEMATANGAN KARIR MAHASISWA - S.A. Lilly Nurrillah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
The background of this research was that there was tendency on the need of guidance and counseling services for improving students’ maturity in the future. The research was aimed at developing a career guidance program for improving students’ career maturity. This study used descriptive method. The samples were second semester students of music, fine art and dance education study programs of Language and Art Education Faculty (FPBS) of UPI in academic yaer 2007-2008. Data collected by utilizing a career maturity instrument developed by the researcher. The research concludes that (1) students’ career maturity was is mature category; (2) there was no guidance services for improving career maturity of students of art education departments of FPBS and UPTLBK UPI; (3) based on result of the research, a career guidance services program for improving student’s career maturity could be formulated.